Cotton productivity enhanced through transplanting and early sowing - Ahmad, Saghir; Iqbal, Muhammad; Muhammad, Taj; Mehmood, Abid; Ahmad, Shakeel; Hasanuzzaman, Mirza (Acta Scientiarum. Biological Sciences, 2018)
Due to high temperatures in arid regions, cotton crop emergence and early establishment of seedlings are adversely affected. Field studies were undertaken to quantify the effects of transplantation of cotton (Gossypium hirsutum L.) seedlings during the early part of the growing season (March) and crop season (May) for potential realization of cotton productivity under the harsh weather of the southern part of Punjab province, Pakistan. Treatments, consisting of (a) two planting dates (March and May), and (b) two sowing methods (transplanting of seedlings and direct seeding), were arranged in a randomized complete-block design with four replications. Results showed that transplanting seedlings improved the productivity of cotton by 14.2% over direct seeding. Productivity was also increased substantially (34.8%) by planting during March over May sowing. The practice of planting cotton by transplanting seedlings and early sowing could be successfully adapted in areas where high temperatures coincide with the May planting and peak blooming periods in different cotton growing areas.